The Influence of Principal Leadership and Work Commitment on Professionalism of Primary School Teachers - Ican Ican; Yasir Arafat; Destiniar Destiniar (research, training and philanthropy institution Natural Aceh, 2021)
This study aims to determine the influence of principal leadership and work commitment to the professionalism of primary school teachers. The formulation of the problem in this study, namely (1) how is the influence of the principal leadership on teacher professionalism?, (2) how is the influence of work commitment on teacher professionalism?, (3) how is the influence between principal leadership and teacher work commitment to teacher professionalism. This study uses a quantitative approach with an ex post facto design. This research is looking for systematic empirical data and in this study the researcher can’t directly control the independent variables because the events have occurred and according to their nature can’t be manipulated. This study places the influence of principal leadership and teacher work commitment to the professionalism of primary school teachers in Cokroaminoto cluster, Semidang Aji District, OKU Regency. The results of the descriptive analysis show that the performance of the Cokroaminoto cluster primary school teachers in good category of 65.5%, that’s, the mean or average score is 61.4155 which in 52–63 interval. The results of the descriptive analysis show that the professionalism of teachers in the professional category of teachers in carrying out their duties is 77.5%. However, there are still teachers whose professionalism is in the quite professional category at 12.0% and even there are still teachers who are less professional in carrying out their duties by 2.8%, this is reflected in the indicator that teachers do not master the methods and evaluation of learning outcomes. Based on the results of multiple regression analysis, the regression equation line Y = 18.668 + 0.260X1 + 0.472X2 is obtained. These results indicate that this positive sign is in accordance with the theory and can be interpreted that the principal leadership and teacher professionalism are good, so the teacher's performance will be good too.